How high is the prevalence of depression in old age? - John Snowdon (Brazilian Journal of Psychiatry, 2002)
Depressive symptoms are highly prevalent in late life - in Brazil and around the world. Some experts have argued that depression is less common in old age, quoting studies that show a lower prevalence of major depression in late life. Results from cross-age studies have been remarkably inconsistent, both regarding which age-group has the peak rate and regarding actual rates. A majority of surveys of the prevalence of depressive conditions in old age (not just major depression), warranting clinical interventions, report it to be over 10%. Physical ill-health is the most significant associated factor, but it may distract doctors from recognising depression. Clinical interventions for late life depression are worthwhile. It is recommended that funding be allocated to training in assessment and management, environmental initiatives to counter feelings of helplessness and lowered self-esteem, and research.